Floods in the TempisqueRiver: History and Social Perceptions (1900-2007) - Pizarro, Yanina (2008)
The present article is about the subject of the floods from the perspective of the environment history, making emphasis on the development of this problem in the course of the twentieth century and concentrated in the populations of Filadelfia, La Guinea, Ortega and Bolsón, all settled in the margins of the Tempisque river. The objective of this work is to demonstrate that floods aren’t new or trigger only by nature, but are also linked to human activities that for decades has used the natural resources of the basin. Likewise, social perceptions are considered like a tool to understand the floods from the position of his inhabitants.